2012
DOI: 10.1016/j.heares.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of isoflurane and ketamine-based anaesthetics on cochlear function in the mouse

Abstract: Isoflurane is a volatile inhaled anaesthetic widely used in animal research, with particular utility for hearing research. Isoflurane has been shown to blunt hearing sensitivity compared with the awake state, but little is known about how isoflurane compares with other anaesthetics with regard to hair cell transduction and auditory neurotransmission. The current study was undertaken in C57Bl/6J and C129/SvEv strains of mice to determine whether isoflurane anaesthesia affects hearing function relative to ketami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 47 publications
4
49
0
1
Order By: Relevance
“…However, it is possible that species or individuals could vary in their response to the anesthesia. Isoflurane, which was used for all birds in this study, has been shown to elevate thresholds compared to a ketamine/xylazine combination in rats and mice, with a reduction in sensitivity over the duration of anesthesia (Cederholm et al 2012; Ruebhausen et al 2012). Deep anesthesia with ketamine, nembutal and halothane reduced or eliminated both cochlear action potentials and distortion products in starlings and chickens (Kettembeil et al 1995).…”
Section: Discussionmentioning
confidence: 96%
“…However, it is possible that species or individuals could vary in their response to the anesthesia. Isoflurane, which was used for all birds in this study, has been shown to elevate thresholds compared to a ketamine/xylazine combination in rats and mice, with a reduction in sensitivity over the duration of anesthesia (Cederholm et al 2012; Ruebhausen et al 2012). Deep anesthesia with ketamine, nembutal and halothane reduced or eliminated both cochlear action potentials and distortion products in starlings and chickens (Kettembeil et al 1995).…”
Section: Discussionmentioning
confidence: 96%
“…P2RX2-null and background strain C57BL/6J WT mice were born and raised either in a quiet environmental chamber or in an environmental chamber with a continuous noise level of 75 dB SPL, 8-16 kHz. Assessments of hearing function were performed using established protocols (39). Mid-modiolar cochlear cyrosections from the quiet-chamber 17-mo old P2RX2-null and WT mice were examined by immunofluorescence confocal microscopy as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were anaesthetized initially by inhaling 4 % isoflurane in an induction chamber. They were then transferred to the manifold and maintained with 1.8 % isoflurane (for young rats) or 1.5 % isoflurane (for aged rats) on a water circulated warming blanket (Kent Scientific) set to 37°C during the whole recording session of 30–60 mins (Cederholm, Froud et al 2012). Stimulus presentation and DPOAE recordings were performed using BioSig (Tucker Davis Technologies, TDT) in the acoustic chamber.…”
Section: Methodsmentioning
confidence: 99%